The Experiential Tourism in Nakhon Pathom Province: From Tourism Resources toward Tourism’s Patterns and Activities - Mulmit, Pimchanok (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research aimed 1) to explore and revise tourist attractions in Nakhon Pathom province, 2) to organize tourist activities and tourist routes for Experiential Tourism according to varied tourism resources. Areas of study include: Mueang Nakhon Pathom, Nakhon Chai Si and Sam Phran district. The research method used by interviewed 50 tourism stakeholders with purposive sampling and the questionnaire was used by 400 Thai tourists with convenience sample. The data obtained from the questionnaire were analyzed by frequency, percentage, mean, and standard deviation. In the interview section, use content analysis. The results were as follows, there were 4 types of tourist attractions in Nakhon Pathom which consisted of agricultural tourist attractions, historical and cultural tourist attractions, religious and beliefs tourist attractions and wellness tourist attractions. Moreover, from a survey of tourist’s attitudes, behaviors and satisfactions, it showed that tourists expected tourist attractions. Furthermore, some factors motivated them to decision to travel which were tourist attractions and activities. Also, they satisfied with attractions, activities, and experiences factors. Consequently, the research findings were analyzed by the outputs of varied tourism resources and the tourist’s behavior and satisfaction that could organize 4 types of tourism and 5 Experiential Tourism routes as: 1) Religious and Beliefs Experiential Tourism 2) Agricultural Experiential Tourism 3) Historical and Cultural Experiential Tourism and 4) Wellness Experiential Tourism. For 5 Experiential tourism routes as: 1) Religious and Beliefs on Pilgrimage journey 2) Historical, Cultural and Sufficiency Economy in Dvaravati territory; 3) Learning farmer lifestyle, Integrated farming for Experiential Tourism; 4) Wellness Experiential Tourism with natural therapy way and 5) Wellness Experiential Tourism with sufficient economy way. Article history : Received 1 August 2018 Revised 14 August 2018 Accepted 22 August 2018 SIMILARITY INDEX = 0.00